Providing Compassionate Off-Ramps for Medical Students Is a Moral Imperative. (May 2019) - Bellini, Lisa M.; Kalet, Adina; Englander, Robert
Abstract : It is highly unusual for learners to leave medical training in the United States even though some individuals' goals may change and others may not achieve expected competence. There are a number of possible reasons for this: (1) Students may feel that they have progressed too far into their careers and amassed too much debt to leave medical training; (2) students may be allowed to graduate despite marginal performance; and (3) students may have entered medical training with risk factors for poor performance that were not addressed. As stewards of the educational process, medical educators have an ethical obligation to students and the public to create off-ramps, or points along the educational continuum at which learners can reassess their goals and educators can assess competence, that allow students to leave medicine. Given the nationwide focus on physician health and wellness, the authors believe the creation of options to leave medical training without compromising one's self-esteem or incurring unmanageable debt (i.e., compassionate off-ramps) is a moral imperative. The practice of medicine should not be an exercise in survival; it should allow people to develop and thrive over the course of their careers. Offering students options to make use of the medical competencies they have accumulated in other attractive careers would enable medical educators to behave compassionately toward individual students and fulfill their societal obligation to graduate competent and committed physicians. To this end, the authors present six recommendations for consideration.